Improve possibilities of the AutoCAD Package for optimization of three –dimensional simulation in building modeling application - Krasnyuk, A. V.; Ulchenko, T. V.; Netesa, A. N.; Netesa, K. N. (Science and Transport Progress, 2011)
AutoCAD 2009 possibilities of the 3D solid-body modeling are described in the article. The optimum design methods for construction drawing tasks are analyzed. The choice of methods for 3D solid-body drawing is proved by samples.